DILEMA DISIPLIN GURU DI ERA HAK ASASI MANUSIA: ANTARA KODE ETIK DAN TANTANGAN PERILAKU SISWA DI SMP 1 ULUJAMI - Sikha Nur Inayah; Windi Nurrohmatul Azizah; Himatunnisa; Nur Khasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teachers' dilemmas in enforcing discipline in the era of human rights, the implementation of the teacher code of ethics, and humanistic disciplinary enforcement strategies at SMP 1 Ulujami. The study used a qualitative approach with descriptive research and case studies. Data were obtained through observation and documentation studies,then analyzed using qualitative descriptive analysis techniques. The results indicate that teachers face a dilemma in enforcing discipline because they must balance assertiveness with respect for students' rights. Challenges in student behavior influenced by technological and social media developments also affect teachers' authority in the learning process. In practice, the implementation of the teacher code of ethics is carried out through a fair, educational, and character-building approach. This study also found that humanistic disciplinary strategies, such as a dialogical approach, providing educational consequences,teacher role models, and collaboration with parents, can create a more conducive learning environment and support positive student character development.